2006
DOI: 10.1108/07363760610674329
|View full text |Cite
|
Sign up to set email alerts
|

Using framing and credibility to incorporate exercise and fitness in individuals' lifestyle

Abstract: PurposeTo investigate the influence of message framing and message credibility on one's attitude and intention toward exercise and fitness activities.Design/methodology/approachA sample of 136 respondents participated in the study. A 2 × 2 factorial design was utilized and tested using multivariate analysis of variance (MANOVA).FindingsThe findings reveal the significance of source credibility for influencing both attitude and intention toward exercise and fitness activities. Additionally, the results reveal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
4
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 28 publications
1
63
4
1
Order By: Relevance
“…Considerable research on persuasion has examined the impact of message framing (i.e., gain vs. loss) on healthrelated behavioral intentions, such as breast self-examinations (Banks et al 1995;Meyerowitz and Chaiken 1987), dieting (Spiegel et al 2004) and exercise (Arora et al 2006;Jones et al 2003). These authors manipulate gain-framed messages by focusing on the benefits that result from performing the behavior described in either a gain or a nonloss situation, such as: "If you get a mammogram, you are likely to find out that your breasts are healthy" (gain) versus "If you get a mammogram, you decrease the risk of an undetected, potentially life-threatening tumor" (nonloss).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Considerable research on persuasion has examined the impact of message framing (i.e., gain vs. loss) on healthrelated behavioral intentions, such as breast self-examinations (Banks et al 1995;Meyerowitz and Chaiken 1987), dieting (Spiegel et al 2004) and exercise (Arora et al 2006;Jones et al 2003). These authors manipulate gain-framed messages by focusing on the benefits that result from performing the behavior described in either a gain or a nonloss situation, such as: "If you get a mammogram, you are likely to find out that your breasts are healthy" (gain) versus "If you get a mammogram, you decrease the risk of an undetected, potentially life-threatening tumor" (nonloss).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…To date, the moderating effect of source credibility has been found in studies on the promotion of goods or services (Arora et al 2006;Jones et al 2004;Kumkale et al 2010;Zhang and Buda 1999). Though examples of studies focused on the role of source credibility in social marketing programs can be found, they are relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…For example, exercise promotion messages presented by a noncredible source resulted in little further consideration of the message, therefore limiting the potential influence of the message (Jones, Sinclair, & Courneya, 2003). Other researchers found that a highly credible source of exercise information (the American Heart Association) positively influenced attitudes and intentions toward exercise behavior (Arora, Stoner, & Arora, 2006). Similarly, citing a non-governmental cancer council as the source improved the success of a sun protection campaign (Smith, Bauman, McKenzie, & Thomas, 2005).…”
mentioning
confidence: 99%